CLOSING THE POLICY GAPS: REVIEWING TOBACCO CONTROL COMMITMENTS IN INDONESIA’S RPJMN 2025-2029 - Patricia Rinwigati; Renny Nurhasana; Astri Hanna Grace Waruwu; Karlina Khairunnisa; Aryana Satrya; Suci Puspita Ratih; Fadhilah Rizky Ningtyas; Risky Kusuma Hartono (Universitas Airlangga, 2026)
Background: The National Medium-Term Development Plan (RPJMN) 2025-2029 is critical in setting the direction for national tobacco control policies. This study aims to analyze the extent to which tobacco control is integrated into the RPJMN 2025-2029 and to identify key gaps and challenges in its formulation. Methods: This study analyzed the 2025-2029 National Medium-Term Development Plan (RPJMN) using a qualitative approach to evaluate tobacco control indicators, both direct and indirect. Thematic analysis, supported by secondary data, was used to identify gaps between policy planning and the reality of tobacco control in Indonesia. Results: The RPJMN 2025-2029 demonstrates awareness, but significant gaps remain. These include unambitious targets for reducing youth smoking, a complex tax structure, limited monitoring of smoke-free areas, unevenly distributed cessation services, and weak regulations on advertising and labeling. Conclusion: Strengthening the commitment to tobacco control in RPJMN requires a more ambitious and integrated approach. The ratification of the Framework Convention on Tobacco Control (FCTC) and the involvement of civil society are strategic steps toward a tobacco-free Indonesia and the achievement of the 2045 Golden Indonesia Vision. Keywords: policy review, RPJMN, tobacco control